An Analysis of Grammatical Errors in Students’ Descriptive Writing Using Surface Strategy Taxonomy - Ismail (Jurnal Pendidikan dan Media Pembelajaran, 2024)
This study basically aimed to explore students’ grammatical errors in writing descriptive paragraph using surface strategy taxonomy. The participants of this qualitative research were first year students of English education department of STKIP Yapis Dompu who took basic writing class in academic year 2023/2024. The researcher analyzed 12 students’ descriptive writings about “Guide Dog” written to meet assignment of “Basic Writing” course. The data of this research then analyzed in the form of percentage. The findings of this research revealed that the most common grammatical errors committed by the students in their descriptive writing were on misformation having number of 34 or 45% of the total numbers of errors that ranked first. This was followed by addition with 22 or 28% that ranked second, misordering with 12 or 16% that ranked third, and omission with 8 or 11% that ranked fourth. Another very important finding was that the most common grammatical errors based on sub category errors were on the usage of verb with 60 or 80% of the total 76. It indicated that almost all students do not really understand the usage of verb in present tense. They often made structurally incorrect sentences. This issue must be given a special attention by all lecturers of English education department of STKIP Yapis Dompu to find solution students' competence to construct correct English sentences will definitely reflect on almost all other English courses such as, academic writing, reading for academic, TOEFL, grammar for TOEFL, listening, and many more courses